2021
DOI: 10.21608/ejvs.2021.51775.1206
|View full text |Cite
|
Sign up to set email alerts
|

The First Report of the Antimicrobial Resistance of Acinetobacter baumannii Isolates from Seafood Samples

Abstract: A cinetobacterbaumannii is a newly-launched bacterium responsible for rare cases of diarrhea and foodborne diseases. This survey was performed to study the prevalence and antimicrobial resistance of A. baumannii isolates recovered from fish, shrimp, and lobster. Five-hundred seafood samples were collected and cultured for isolation of A. baumannii. A. baumannii isolates were identified by biochemical tests and further confirmed by the PCR. The antimicrobial resistance of isolates was studied using disk diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…In our previous survey [27], A. baumannii prevalence amongst the fish, shrimp, and lobster samples was 10%, 5.30%, and 2.50%, respectively. Hasiri et al found A. baumannii in 5.6% seafood in Iran.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous survey [27], A. baumannii prevalence amongst the fish, shrimp, and lobster samples was 10%, 5.30%, and 2.50%, respectively. Hasiri et al found A. baumannii in 5.6% seafood in Iran.…”
Section: Discussionmentioning
confidence: 80%
“…This low prevalence in Iran indicates that A. baumannii contamination of seafood is emerging. In this study, samples were collected only from seafood markets in central Shiraz, so this low prevalence is not representative of the whole province, and different results could be found in other seafood markets [27]. In the United States [41], Acinetobacter was detected in 9.54% of retail seafood samples.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation